Escaping from Hunger before WW1: Nutrition and Living Standards in Western Europe and USA in the Late Nineteenth Century - Ian Gazeley; Rose Holmes; Andrew T. Newell; Kevin Reynolds; Hector Gutierrez Rufrancos (Institute of Labor Economics (IZA), 2017)
We estimate calories available to workers' households in the USA, Belgium, Britain, France and Germany in 1890/1. We employ data from the United States Commissioner of Labor survey (see Haines, 1979) of workers in key export industries. We estimate that households in the USA, on average, had about five hundred daily calories per equivalent adult more than their French and German counterparts, with Belgian and British workers closer to the USA levels. We ask if that energy bonus gave the US workers more energy for work, and we conclude that, if stature is taken into account, workers in the US and UK probably had roughly the same level energy available for work, whereas the German and French workers most likely had significantly less. Finally we ask economic migration leads to taller children. To answer that we estimate the influence of children on calorie availability among ethnically British workers in the USA and, separately, among British workers in Britain. We find that US-based British households are at least as generous in terms of the provision of calories to their children as their Britain-based counterparts. Other things equal, this means that US-based British children would grow taller.
Keywords: J11; J61; N30; 330; living standards; nutrition; international comparisons; migration